1,1-digoldallylium complexes: diaurated allylic carbocations indicate new prospects of the coordination chemistry of carbon - Mulks, Florian; Antoni, Patrick W.; Gross, Jürgen H.; Graf, Jürgen; Rominger, Frank; Hashmi, A. Stephen K. (Journal of the American Chemical Society, 2019)
Reacting (NHC)(cyclopropenyl)gold(I) complexes with cationic gold complexes [(IPr)AuX] afforded extremely reactive allylium-1,1-diido-bridged digold intermediates. We prove the existence and constitution of this structure with FT-ICR-MS/MS, NMR, and UV-vis-NIR experiments and isolated the nucleophilic addition product [(Me)(Ph)(CCHC){Au(IPr)}2(SOMe2)]NTf2 with DMSO. Our computational investigation unveiled that the bonding situation of this μ-allylium-1,1-diido digold domain was best described as a three-center-four-electron bond with a π-backbond. The valence orbitals showed extreme delocalization and strong π-interactions between the three centers Au1-C1-Au2. The bridging carbon atom C1 was best described as trigonal planar sp-hybridized carbon in this structure. Excitation succeeded in UV-vis-NIR measurements with energies as low as near-IR radiation.